The variability of stratospheric and mesospheric NO2 in the polar winter night observed by LIMS - Russell, M. J., III; Remsberg, E. E.; Callis, L. B.; Solomon, S.; Gordley, L. L. (1984)
The LIMS experiment sounded the upper atmosphere from late October 1978 to late May 1979 and provided vertical profiles of atmospheric temperature, 03, H2O, HNO3, and NO2. Radiance averaging was used before retrieval to measure the altitude distribution of NO2 over the altitude range from the lower stratosphere into the mesosphere. Observations in the polar winter night region northward of about 70 deg N reveal NO2 levels near 175 ppbv at about 70 km, and they show a significant longitudinal variability (factor of 4 to 7). A definite temporal trend exists, showing a buildup of mesospheric and stratospheric NO2 during the polar night and a subsequent slowing of the increase of decline after sunlight returns, depending on altitude. The data represent the first experimental evidence that the thermosphere is an NO(x) source for the mesosphere and stratosphere.